2009
DOI: 10.1167/9.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal convergence in early contrast vision: Binocular summation is followed by response nonlinearity and area summation

Abstract: We assessed summation of contrast across eyes and area at detection threshold (C(t)). Stimuli were sine-wave gratings (2.5 c/deg) spatially modulated by cosine- and anticosine-phase raised plaids (0.5 c/deg components oriented at +/-45 degrees ). When presented dichoptically the signal regions were interdigitated across eyes but produced a smooth continuous grating following their linear binocular sum. The average summation ratio (C(t1)/([C(t1+2)]) for this stimulus pair was 1.64 (4.3 dB). This was only slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 24 publications
8
49
0
Order By: Relevance
“…Previous detailed analyses (Meese, 2010;Meese & Summers, 2007, 2009) have consistently shown that spatial probability summation across the elements of our standard size filter (spatial frequency bandwidth of 1.6 octaves, orientation bandwidth of T25-, 4-lobe sinephase receptive field) cannot account for our results. This was confirmed again here as follows.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Previous detailed analyses (Meese, 2010;Meese & Summers, 2007, 2009) have consistently shown that spatial probability summation across the elements of our standard size filter (spatial frequency bandwidth of 1.6 octaves, orientation bandwidth of T25-, 4-lobe sinephase receptive field) cannot account for our results. This was confirmed again here as follows.…”
Section: Resultsmentioning
confidence: 50%
“…The Swiss cheese stimulus was designed to combat this problem (Meese & Summers, 2007), at least in part. For example, if the check size is small compared to the rate at which sensitivity declines with eccentricity, then each type of cheese ("black" and "white") are spread fairly equally over the inhomogeneity, with the net result that sensitivity is fairly equal for the two (Meese & Baker, 2011;Meese & Summers, 2007, 2009. However, if the check size is large compared to the rate of decline, then the size of the integration aperture might be underestimated because the loss of sensitivity in the peripheral hole regions would mean that there is little benefit from filling them in.…”
Section: Basic Intuitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of consensus probably springs, in part, from the smallness of these effects -just a few dB -coupled with the considerable difficulty of getting reliable, unbiassed threshold estimates to the required accuracy. Over the last 30 years, computer-controlled, forced-choice psychophysical methods with better display technology, and much greater numbers of trials, have improved the reliability of threshold estimation, and with these methods estimates of the binocular advantage tend to cluster around 4-5dB (Legge, 1984;Maehara & Goryo, 2005;Meese & Baker, 2011;Meese et al, 2006;Meese & Summers, 2009;Simmons & Kingdom, 1998;Simmons, 2005) -as if forming a compromise between the theoretically salient values of 3 and 6 dB (which represent an ideal observer with independent noise in the two eyes versus linear summation with fixed noise). In a retrospective analysis, however, we found that the variation between studies may not be random.…”
Section: Relation To Binocular Summation Of Luminance Contrastmentioning
confidence: 99%